PELATIHAN PENYUSUNAN LEMBAR KERJA SISWA (LKS) BERBASIS QR-CODE BAGI GURU MGMP OTKP KOTA SURABAYA - LIfa Panduwinata; Brilian Rosy; Fitriana Rahmawati; Heny Kusdiyanti (Cv. Utility Project Solution, 2022)
Based on a 2021 survey of 346 Governance and Office Automation (OTKP) teachers in Surabaya showed that 47.1% (163 teachers) needed training in developing teaching materials. LKS, which is teaching material, is an important part where teachers must be able to design LKS as a learning resource that integrates four essential things, including Strengthening Character Education (PPK), Literacy, 21st Century Skills, and Higher Order Thinking Skills (HOTS). The application of technology into learning resources can be done one way by integrating Quick Response Code technology, called a QR Code, into worksheets. This PKM activity uses interactive lecture methods, discussions, demonstrations, training, and mentoring. The results of this PKM activity received a very good response which can be seen from the activity evaluation sheet, and the testimonies of the teachers participating in the training, 93% of the participants who took part in this activity stated that they gained more knowledge regarding how to compile good and correct QR-Code Based LKS. As well as 53.7% of the participants who participated in this activity stated that they would develop a QR-Code Based LKS per the subject being taught.